On-road driving assessment and route design for drivers with dementia. (February 2015) - Berndt, Angela H; May, Esther; Darzins, Peteris
Introduction: Dementia causes the progressive loss of cognitive capacities and thus impairs social and daily living skills. Dementia, to varying degrees, influences driver performance and safety. Eventually drivers affected by dementia must stop driving so they do not harm themselves or others. However, having to stop driving can result in loss of mobility and social connections. Therefore, assessing drivers with dementia is important. Driving assessment is susceptible to possible biases, including unreliable driving performance measures or driving routes that are inconsistent in the levels of difficulty of the driving tasks and manoeuvres. The aim of the study was to determine what measures of driving performance could optimally be applied to occupational therapy on-road driving assessments. Method: All drivers with dementia underwent a 60 minute, set route on-road driving assessment that consisted of 110 pre-programmed observation points. Results: The study identified 80 sufficiently challenging driving tasks and described the relationship of driving error to that task, for example, critical errors at unguided intersections. Conclusion: The results of the task-demand by error type analysis identified a list of task items that can be applied to assessment route design to increase consistency of on-road assessment for people with dementia.